Tuberculosis and TNF-α inhibitors in children: how to manage a fine balance - Parigi, Sara; Licari, Amelia; Manti, Sara; Marseglia, Gian Luigi; Tosca, Maria Angela; Miraglia del Giudice, Michele; Caffarelli, Carlo; Calvani, Mauro; Martelli, Alberto; Cardinale, Fabio; Cravidi, Claudio; Duse, Marzia; et al. (Acta Biomedica Atenei Parmensis, 2020)
Since the introduction of biologic response modifiers (BRMs) in the management of children affected by the immune-mediated inflammatory disease, these patients substantially improved their quality of life. BRMs are generally well tolerated and effective in most children and adolescents refractory to conventional immunosuppressive therapy. On the other hand, patients receiving BRMs, especially TNF-α inhibitors, display an increased risk of primary infections or reactivations, i.e. due to Mycobacterium tuberculosis. M. tuberculosis can cause severe disease with consequent short- and long-term morbidity in children on anti-TNF-α treatment. The present paper analyses the increased risk of reactivation of latent tuberculosis infection (LTBI) or de novo TB infection in children treated with TNF-α inhibitors, with the purpose to provide recommendations for screening strategies and safety monitoring of paediatric patients. Special attention is also given to the currently available TB screening tools (IGRAs and TST) and their utility in the diagnosis of LTBI before starting the biologic therapy and during the treatment. Finally, the paper analyses the suggested TB-preventing therapies to adopt in these children and the correct timing to overlap anti-TB and anti-TNF-a treatment.